Características ultraestruturais do segmento abdominal da aorta de rato albino - De Mello, Josiane Medeiros; Torrejais, Márcia Miranda; Matheus, Selma Maria Michelin [UNESP]; Domeniconi, Raquel Fantin [UNESP]; Simões, Karina; Orsi, Antonio Marcos [UNESP] (Universidade Estadual de Maringa, 2007)
The objective of the present research was to investigate the ultrastructural peculiarities of the aortic wall of the rat. Seven young adult rats were used, from which fragments of the infrarenal abdominal aorta were collected. After collection, the vascular segments were fixed and sent for analysis by scanning electron microscope. The elastic lamellae appear interposed with smooth muscular fibers; this pattern was verified mainly at the medial layer structure. Among the mural elements a well defined interrelationship was established through connective lamellae of the arterial wall. The collagen lamellae mainly provided anchoring among the elastic and smooth muscular constituents. The intimal layer showed special ultrastructural features, such as a non-continuous inner elastic lamina presented in certain sites of the vascular wall, followed by endothelial pores. This mural pattern of the abdominal aorta provided support to vascular functions such as shrinkage among the laminar composition of the arterial layers, also acting in mechanical properties of the vascular wall, such as viscoelasticity and contractility - essential actions to blood vessel hemodynamics.
Mural features of the abdominal aortic segment of albino rat
Keywords: Abdominal aorta; Albino rat; Ultrastructure; collagen; abdominal aorta; animal experiment; animal model; animal tissue; aorta wall; artery constriction; artery intima; cell ultrastructure; controlled study; elasticity; fibroelastoma; hemodynamics; nonhuman; rat; scanning electron microscope; smooth muscle; smooth muscle contractility; tissue distribution; viscoelasticity; Rattus